2014
DOI: 10.1158/2326-6066.cir-13-0199-t
|View full text |Cite
|
Sign up to set email alerts
|

IL32 Is Progressively Expressed in Mycosis Fungoides Independent of Helper T-cell 2 and Helper T-cell 9 Polarization

Abstract: Mycosis Fungoides (MF), the most common type of cutaneous T-cell lymphoma (CTCL) is characterized by a helper T cell 2 (Th2)-skewing with a mature CD4+ memory T-cell phenotype. Using skin samples from MF patients (n=21), healthy volunteers (n=17), individuals with atopic dermatitis (n=17) and psoriasis (n=9), we found interleukin (IL)-32 mRNA expression significantly higher in MF samples than in samples from benign inflammatory skin diseases, and its expression increases with disease progression. By immunohist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…We previously showed that IL-4 mRNA expression levels in MF skin were not significantly higher than those in healthy volunteers. 7 Additionally, we confirm that MF skin shows significantly higher GM-CSF mRNA expression compared to healthy volunteers (Fig. S1).…”
Section: Il-32 Induces Cd14supporting
confidence: 69%
See 2 more Smart Citations
“…We previously showed that IL-4 mRNA expression levels in MF skin were not significantly higher than those in healthy volunteers. 7 Additionally, we confirm that MF skin shows significantly higher GM-CSF mRNA expression compared to healthy volunteers (Fig. S1).…”
Section: Il-32 Induces Cd14supporting
confidence: 69%
“…Previously, we 7 and others 8,9 reported that IL-32, a proinflammatory cytokine, is highly and progressively expressed in MF skin. We also showed that MF tumor cells are regarded as the most probable candidates for expressing IL-32.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Interferon-γ and interleukin (IL)-32 mRNA expression levels are increased in MF skin compared to normal and benign inflammatory dermatoses [28] . In vitro, IL-32 inhibits HSV-2 growth in epithelial Vero cells [29] .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ohmatsu et al [35] demonstrates elevated interleukin-32 mRNA expression levels in mycosis fungoides and suggests that interleukin-32 might contribute to the disease progression. Another study from Singer et al [36] reports on elevated serum levels of interleukin-31 in 14 of 26 pruritic Sézary syndrome patients.…”
Section: Recent Immunological Studiesmentioning
confidence: 99%